An Integrated Fluency and Psychosocial Treatment for Adults Who Stutter: Addressing Stuttering and Self-Efficacy with Acceptance and Commitment Therapy - Hart, Alice Kathleen (Curtin University, 2022)
This thesis presents a novel and integrated fluency and psychosocial intervention for adolescents and adults who stutter, combining traditional fluency treatment techniques with Acceptance and Commitment Therapy. The intervention was designed to simultaneously and holistically address the speech fluency and self-efficacy needs of adults who stutter. Significant improvements were found across speech fluency, self-efficacy, psychological flexibility, and overall psychosocial well-being. These positive findings may inform speech-language pathologists' clinical management of stuttering disorders in the future.